Study of dielectric properties and the molecular dynamics using Raman spectroscopy in pure and nanoparticle doped liquid crystal compound, 6O.4. (24th March 2017) - Gogoi, Binod; Singh, Keisham Nanao; Mishra, Ramanuj; Ghosh, T. K.; Bhattacharjee, Ayon; Alapati, Parameswara Rao
ABSTRACT: A comparative study on the dielectric properties (in 100 Hz to 40 MHz frequency range) of a pure and silver nano particle dispersed (0.25% and 0.50% by weight) Liquid crystal compound, 6O.4 and the resultant changes at the molecular level using Laser Raman Spectroscopy is reported. The dielectric anisotropy of the two samples was found to be negative but the magnitude of the anisotropy slightly decreased due to the dispersion of the nanoparticles and the relaxation frequency in nematic phase was found to increase with the temperature and the concentration of nanoparticles. Raman spectroscopy studies on pure and SNP dispersed 6O.4 confirms the modification in molecular polarizability in SNP dispersed sample.